Optical signaling in biofluids: a nondenaturing photostable molecular probe for serum albumins. Issue 9 (17th December 2015) - Dey, Gourab; Gaur, Pankaj; Giri, Rajanish; Ghosh, Subrata
Abstract : Conceptually new molecular designs as nondenaturing emissive materials for the detection and quantification of serum albumins in biofluids. Abstract : The systematic investigation of the interaction of a new class of molecular materials with proteins through structure–optical signaling relationship studies has led to the development of efficient fluorescent probes that can detect and quantify serum albumins in biofluids without causing any denaturation.